2014
DOI: 10.1002/cbin.10301
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs with low expression levels in cells are enriched in secreted exosomes

Abstract: Long non-coding RNAs (lncRNAs) are involved in regulating chromatin modifications, gene transcription, mRNA translation, and protein function. We recently reported a high variation in the basal expression levels of a panel of lncRNAs in HeLa and MCF-7 cells and their differential response to DNA damage induction. Here, we hypothesized that lncRNA molecules with different cellular expression may have a differential abundance in secreted exosomes, and their exosome levels would reflect cellular response to DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
228
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(232 citation statements)
references
References 24 publications
4
228
0
Order By: Relevance
“…In esophageal squamous cell carcinoma, TUG1 promoted proliferation and migration in vitro [18]. Gezer et al found that TUG1 were highly enriched in secreted exosomes of HeLa and MCF-7 cells [22]. These data suggested that TUG1 may promote cancer progression.…”
Section: Discussionmentioning
confidence: 98%
“…In esophageal squamous cell carcinoma, TUG1 promoted proliferation and migration in vitro [18]. Gezer et al found that TUG1 were highly enriched in secreted exosomes of HeLa and MCF-7 cells [22]. These data suggested that TUG1 may promote cancer progression.…”
Section: Discussionmentioning
confidence: 98%
“…One hypothesis suggests that lncRNAs that are stable in human plasma are protected by exosomes (19). It has been demonstrated that exosomes serve an important role in the protection and secretion of non-coding RNAs, including miRNAs and lncRNAs (20,21), and cells affected by stimuli, such as oxidative stress, may increase the secretion of exosomes (22,23). In addition, GC cells are able to release related RNAs into the extracellular environment via exosomes during tumorgenesis (24).…”
Section: Discussionmentioning
confidence: 99%
“…16) A recent study showed that ncRNAs were highly abundant in exosomes secreted by HeLa and MCF-7 cell lines. 29) More recently, ncRNAs of human urinary exosomes were analyzed using NGS. 20) Thus, these results show that exosomes can entrap many types of RNAs and potentially transfer large amounts of information between cells.…”
Section: Discussionmentioning
confidence: 99%